2016
DOI: 10.33371/ijoc.v10i1.411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Klinis dan Manajemen Kanker Penis di Rumah Sakit Sardjito, Yogyakarta

Abstract: The aim of this study to evaluate clinical and management of penile cancer patients at Sardjito Hospital. Data were collected from medical record of Sardjito Hospital from 2006 - 2013. The clinical factors and therapy were studied from each patient. Correlation between age and stadium of disease were analyzed using Chi-Square Test while the correlation among pathological grade and T, N and M stage were analyzed by using Fisher Test. There are 35 cases of penile cancer with mostly of 40-60 years old man (45.7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
2
Order By: Relevance
“…According to these guidelines, partial penectomy is recommended when the cancer is at stage T2. In contrast, at stage T3, total penectomy and perineal urethrostomy are performed (Prayoga & Tranggono, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…According to these guidelines, partial penectomy is recommended when the cancer is at stage T2. In contrast, at stage T3, total penectomy and perineal urethrostomy are performed (Prayoga & Tranggono, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…7 In Indonesia, the research conducted at Sardjito Hospital from 2006 to 2013 found 35 cases of penile cancer, in which most commonly affects men between the ages of 40-60 years (45.7%). 8 Another study done at Cipto Mangunkusumo Hospital and Dharmais Cancer Hospital from October 1994 to September 2005 found 69 cases of penile cancer, in which most commonly affects men between the ages of 40-50 years old. 9 In this study, among 65 penile cancer patients from 2011 to 2015, most commonly affects men between the ages of 40-49 years, with only 12% at ages <40 years.…”
Section: Discussionmentioning
confidence: 99%
“…9 In Indonesia, the research conducted at Sardjito Hospital from 2006 to 2013 found 35 cases of penile cancer, in which most commonly affects men between the ages of 40-60 years (45.7%). 10 Another study done at Cipto Mangunkusumo Hospital and Dharmais Cancer Hospital from October 1994 to September 2005 found 69 cases of penile cancer, in which most commonly affects men between the ages of 40-50 years old. 11 In this study, penile cancer most commonly affects men between the ages of 40-49 years, with only 12% at ages <40 years.…”
Section: Discussionmentioning
confidence: 99%